2004
DOI: 10.1001/archneur.61.7.1104
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Assessment Battery and Differential Diagnosis of Frontotemporal Dementia and Alzheimer Disease

Abstract: Background: The different distribution of pathologic features in frontotemporal dementia (FTD) and Alzheimer disease (AD) predicts a predominant dysexecutive syndrome in FTD. The Frontal Assessment Battery (FAB) has previously been validated in diseases associated with a frontal lobe dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
159
3
13

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(195 citation statements)
references
References 22 publications
9
159
3
13
Order By: Relevance
“…The FAB provides a useful screening instrument for executive dysfunction as shown in several clinical investigations, including studies on Parkinson's disease, Alzheimer's disease, or stroke 20, 43, 44. Brain imaging studies revealed positive correlations of decreased FAB scores indicating executive dysfunction and reductions of brain tissue perfusion located to the left middle frontal gyrus and the right superior frontal gyrus in patients with MCI, Alzheimer's disease, and frontotemporal lobe dementias 45, 46, 47.…”
Section: Discussionmentioning
confidence: 99%
“…The FAB provides a useful screening instrument for executive dysfunction as shown in several clinical investigations, including studies on Parkinson's disease, Alzheimer's disease, or stroke 20, 43, 44. Brain imaging studies revealed positive correlations of decreased FAB scores indicating executive dysfunction and reductions of brain tissue perfusion located to the left middle frontal gyrus and the right superior frontal gyrus in patients with MCI, Alzheimer's disease, and frontotemporal lobe dementias 45, 46, 47.…”
Section: Discussionmentioning
confidence: 99%
“…Results are unclear with regard to the Comprehension subtest (Butters, Goldstein, Allen & Shemansky, 1998;Peavy et al, 2001;Randolph et al, 1993). Since the Similarities subtest requires both memory functions and executive processing (Dobbins & Russell, 1990;Insingrini & Vazou, 1997;Slachevsky et al, 2004), it is not likely that the VaD and AD patients can be distinguished on this task. Also, the Arithmetic test might be more impaired in AD patients (Hirono et al, 1998), but arithmetic functions equally require frontal related processes (Dehaene, Molko, Cohen & Wilson, 2004;Rivera, Menon, White, Glaser & Reiss, 2002), such as working memory.…”
Section: Methodsmentioning
confidence: 99%
“…It consists of six subtests assessing conceptualization, cognitive fl exibility, motor programming, sensitivity to interference, motor inhibitory control, and prehension behavior. The authors of the FAB have proposed this test for the evaluation of different kinds of frontal dysfunction, and also to distinguish between neurological pathologies such bvFTD and AD (Slachevsky et al, 2004 ). They report correlations with executive measures such as the Wisconsin Card Sorting Test (WCST) and measures of general cognitive functioning (Mattis Dementia Scale), while highlighting the lack of correlation with the Mini Mental State Examination (MMSE).…”
Section: Introductionmentioning
confidence: 99%